The Life cycle Assessment of Sugarcane: A case study of Amir Kabir Cultivation & Industry - Marashi, Seyedeh Fatemeh; Jaafarzadeh, Neemat; Khorasani, Nematollah; Monavari, Seyed Masoud (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2017)
Assessing life cycle is widely used for estimating energy consumption and environmental loads of goods and services. One of applications of this method is to assess the environmental effects of food products. Due to high demand for sugar in Iran market, the role of sugarcane is very significant in Iran sugar supply. The aim of this study is to assess environmental effects of producing a tone of sugar in Amir Kabir cultivation and industry in Khuzestan. Based on ISO standard, five classes of environmental effects were assessed including Abiotic depletion, eutrophication, acidification, global warming and ozone layer depletion according to the CML method. The data of current study has been collected of Amir Kabir cultivation and industry through in person interview as well as questionnaire in 2015. Background data has been extracted from eco-invent database. Based on the results for eutro- phication 4.6 kg PO4---, acidification potentials 94.91 kg SO2, global warming 1701.76 kg equivalent carbon dioxide and abiotic depletion 0.000087 kg Sbeq and ozone layer depletion 28 milliliters of CFC are released into the environment. The results indicated that producing sugarcane, electricity and burning herbal remnants were the main contributors to the abovementioned effect classes for per ton of sugarcane.